MANAJEMEN KINERJA GURU RAUDHATUL ATHFAL (RA) BERPRESTASI DI YOGYAKARTA - Fu`ad Arif Noor (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2020)
This research was conducted to find out what RA achievers have done so that they can inspire other teachers, with a qualitative method of psychological approach that is carried out directly on the subject under study, in order to obtain all data relating to the performance management of outstanding teachers so that in managing their performance they become teachers an example for fellow teachers. Data collection uses interviews, documentation, and observation. Data analysis techniques include reducing data, presenting, drawing conclusions and verifying. Data validity test is done by triangulation techniques.The research succeeded in revealing the performance of RA achievers in Yogyakarta, there were 6 (six) steps taken by RA achievers, namely: 1) Knowing that there were still deficiencies in performance, 2) Recognizing weaknesses and deficiencies in the seriousness of teaching, 3) Identifying what was the cause first drawbacks related to the performance itself, 4) Developing the performance plan presented, 5) Assessing the problem has been resolved or not (problem solving), and 6) Starting from the beginning again, if needed and needed again.